(untitled) (Research, Society and Development, 2024)
Generalized Anxiety Disorder (GAD) is characterized by excessive and difficult-to-control worries that cause significant distress and impair various aspects of an individual’s life. The search for effective treatment strategies is crucial to alleviate symptoms and improve patients’ quality of life. The aim of this study is to elucidate the pathophysiology of anxiety and identify the different treatments for GAD. The methodology includes an integrative literature review, using databases such as PubMed Central®, SciELO, and Virtual Health Library. Articles addressing GAD and its therapies were selected. Cognitive-Behavioral Therapy (CBT) stands out as the first-choice therapy, complementing the use of drugs and lifestyle changes. Medications from the selective serotonin reuptake inhibitors (SSRIs) class emerge as the main option due to their excellent efficacy and milder adverse effect profile. In summary, an integrated approach combining pharmacological treatment, non-pharmacological interventions, and phytotherapy treatments is crucial for the effective management of anxiety disorders. Thus, these multifaceted strategies aim to comprehensively address the challenges of anxiety, promoting more robust and resilient mental health.